2013
DOI: 10.3389/fnhum.2013.00822
|View full text |Cite
|
Sign up to set email alerts
|

How culture influences perspective taking: differences in correction, not integration

Abstract: Individuals from East Asian (Chinese) backgrounds have been shown to exhibit greater sensitivity to a speaker’s perspective than Western (U.S.) participants when resolving referentially ambiguous expressions. We show that this cultural difference does not reflect better integration of social information during language processing, but rather is the result of differential correction: in the earliest moments of referential processing, Chinese participants showed equivalent egocentric interference to Westerners, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 26 publications
2
49
2
1
Order By: Relevance
“…However, the bilingual students were better at correcting this interference later in their language processing. This re-analysis supports the view that the results of Wu and Keysar (2007) reveal an EF advantage of bilingual participants in their sample, and not necessarily a difference in perspective between East Asian and Western cultures, as claimed by Wu and Keysar (2007) and Wu et al (2013).…”
Section: Could Bilingualism Help Theory Of Mind Development?supporting
confidence: 71%
See 1 more Smart Citation
“…However, the bilingual students were better at correcting this interference later in their language processing. This re-analysis supports the view that the results of Wu and Keysar (2007) reveal an EF advantage of bilingual participants in their sample, and not necessarily a difference in perspective between East Asian and Western cultures, as claimed by Wu and Keysar (2007) and Wu et al (2013).…”
Section: Could Bilingualism Help Theory Of Mind Development?supporting
confidence: 71%
“…It has indeed been shown that performance in the Director task is dependent on EF as participants have to selectively focus their attention on the objects that the Director can see on the grid (Brown-Schmidt, 2009;Lin et al, 2010;Symeonidou et al, 2016;Rubio-Fernández, 2016). Wu et al (2013) re-analyzed the eye-tracking data from Wu and Keysar (2007) and found that the bilingual Chinese students suffered a similar interference from their own perspective as the American students. However, the bilingual students were better at correcting this interference later in their language processing.…”
Section: Could Bilingualism Help Theory Of Mind Development?mentioning
confidence: 99%
“…Previous studies have reported that individuals from Chinese backgrounds have been shown to exhibit greater sensitivity to a third-person perspective than Western participants when resolving referentially ambiguous expressions (Cohen and Gunz, 2002;Wu and Keysar, 2007;Luk et al, 2012;Wu et al, 2013). Thus, one possibility is that the Chinese healthy participants in the present study used a strategy of focusing on the female's perspective throughout; this would increase errors when responding to perspective-switching instructions on the control task.…”
Section: Discussionmentioning
confidence: 61%
“…For adults, at least, this suggests that listeners have little difficulty calculating the speaker's perspective, and indeed have done so prior the point at which this information can be used. In contrast, Barr (2008) suggests that integrating this perspective information with the speaker's message in order to resolve reference is relatively difficult and prone to interference from listener's egocentric point of view (see Wu, Barr, Gann, & Keysar, 2013, for supporting evidence). It cannot be assumed that children will calculate perspectives as readily as adults, and so distinguishing between possible sources of difficulty in perspective calculation or perspective use is important for understanding when and why children might make egocentric errors in natural communication.…”
Section: Introductionmentioning
confidence: 97%